Organic agriculture: Controversies and global development issues in Africa - (:unkn) unknown (My University, 2020)
Organic agriculture offers several options for documenting technological transitions towards new production models, although there are some controversies: low yields, access to standards, effective ecological balance, increased labour... By mobilizing different situations in sub-Saharan Africa, this thematic issue of Cahiers Agricultures provides information on these controversies. The presented papers illustrate how the organic agriculture defined by the standards of industrialized countries cannot reflect the diversity of African agricultural realities. As a result, the need for new certifications and applications for local companies is emerging. However, this emergence is constrained by the lack of comparative knowledge of productive realities between organic and conventional agriculture. Methodological innovations to reduce asymmetries in knowledge about performance comparison are then proposed. The results question the need for new indicators integrating nutrition and health security issues. They show that organic agriculture may also be a mean for increasing yields when the forest rent has been destroyed by export agriculture. While shedding light on the controversies, this thematic issue makes the hypothesis that, under certain conditions, organic agriculture is a breaking opportunity for a technological paradigm that meets the development issues in Africa. It invites us not to confuse this break with the mechanisms of agro-ecology-driven incremental transition.
Keywords: African Research